How effective are technical rules in predicting the 2008 global financial crisis? The case of the four Asian tigers. Issue 1 (2nd January 2021) - Kung, James J.; Lin, Wen-Ying; Chen, Hsiu-Li
Abstract: Many market technicians claim that technical rules are effective more in bear markets than in bull markets. Using the 2008 financial crisis as the backdrop for testing, this study investigates how effective they are in the stock markets of Hong Kong, Korea, Singapore and Taiwan. Accordingly, this study performs three tasks. First, it examines the transmission mechanism of stock market movements between the U.S. market and the four Asian markets using vector autoregression. Second, it employs three technical rules - simple moving average, dual moving average, and trading range break - and evaluates their effectiveness in the four markets. Third, it uses the bootstrap method for statistical inferences about the returns from using these technical rules. This study concludes with some important policy implications for the four Asian markets.